1988
DOI: 10.1128/aac.32.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ribavirin aerosol in mice

Abstract: The pharmacokinetics of ribavirin administered in single or multiple treatments to mice by small-particle aerosol were monitored in lung, serum, and brain tissues. Ribavirin aerosol was administered with a standard drug concentration (20 mg/ml) in the reservoir for 12 h or a high dose (60 mg/ml) for 2 or 4 h. After single or 3-day treatments, ribavirin rapidly accumulated in the lungs at concentrations sufficient to inhibit influenza virus or respiratory syncytial virus (1 to 5 mM). While peak levels of ribavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
(26 reference statements)
2
12
0
Order By: Relevance
“…We have previously shown that ribavirin administered by small-particle aerosol (SPA) reaches the brain and achieves concentrations which should be sufficient for antiviral effectiveness (4,8). However, parenteral administration of ribavirin was not compared.…”
Section: * Corresponding Authormentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that ribavirin administered by small-particle aerosol (SPA) reaches the brain and achieves concentrations which should be sufficient for antiviral effectiveness (4,8). However, parenteral administration of ribavirin was not compared.…”
Section: * Corresponding Authormentioning
confidence: 99%
“…In this report, we describe the pharmacokinetics and effects of ribavirin and ribavirin-2',3',5'-triacetate SPA treatment. Mice were placed in sealed plastic cages and exposed to aerosols as described previously (4,21). The aerosol generator and particle characteristics were the same as previously described (7,20).…”
Section: * Corresponding Authormentioning
confidence: 99%
See 3 more Smart Citations